2021
DOI: 10.1128/spectrum.01109-21
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum and Helminth Coinfections Increase IgE and Parasite-Specific IgG Responses

Abstract: Coinfection with Plasmodium falciparum and helminths may impact the immune response to these parasites because they induce different immune profiles. We compared the antibody profile between groups of Mozambican individuals defined by P. falciparum and helminth previous exposure and/or current infection.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 77 publications
0
12
2
Order By: Relevance
“…Although P. falciparum does not appear to have any effect on H. nana intensity and vice versa, co-infection of P. falciparum with H. nana presented a grievous impairment to the anti-GMZ2 IgG response, which is consistent with experimental evidence that implicates H. nana , a human tapeworm, and rodent one (Hymenolepis diminuta) in dampening the immune response ( 33 ). This, however, contrasts sharply with a couple of earlier reports ( 21 , 34 ). The differential outcome may be attributed to the study designs as helminth positive groups reported, and age of the study participants which influences parasites carriage and immunity to either group of parasites ( 34 ) could have impacted on the results.…”
Section: Discussioncontrasting
confidence: 99%
“…Although P. falciparum does not appear to have any effect on H. nana intensity and vice versa, co-infection of P. falciparum with H. nana presented a grievous impairment to the anti-GMZ2 IgG response, which is consistent with experimental evidence that implicates H. nana , a human tapeworm, and rodent one (Hymenolepis diminuta) in dampening the immune response ( 33 ). This, however, contrasts sharply with a couple of earlier reports ( 21 , 34 ). The differential outcome may be attributed to the study designs as helminth positive groups reported, and age of the study participants which influences parasites carriage and immunity to either group of parasites ( 34 ) could have impacted on the results.…”
Section: Discussioncontrasting
confidence: 99%
“…P . falciparum infection was determined at the Barcelona Institute for Global Health (ISGlobal) (Spain) by 18S ribosomal RNA gene detection through qPCR from dried blood spot (DBS) samples as previously described [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…A detailed explanation of the antigen panel and serum elution procedure from DBS used for this analysis is described in Santano et al . 2021 [ 28 ]. Eluted serum was used to measure total IgE and antigen-specific IgG by quantitative suspension array technology (qSAT) using xMAP Luminex technology against a panel of 27 antigens: 16 from P .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations